2020
DOI: 10.1186/s12865-020-00380-x
|View full text |Cite
|
Sign up to set email alerts
|

Genomic, microbial and environmental standardization in animal experimentation limiting immunological discovery

Abstract: Background: The use of inbred mice housed under standardized environmental conditions has been critical in identifying immuno-pathological mechanisms in different infectious and inflammatory diseases as well as revealing new therapeutic targets for clinical trials. Unfortunately, only a small percentage of preclinical intervention studies using well-defined mouse models of disease have progressed to clinically-effective treatments in patients. The reasons for this lack of bench-to-bedside transition are not co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 145 publications
0
6
0
Order By: Relevance
“…Santi-Roca (2017) [ 59 ] observed that BALB/c mice infected with different strains of T. cruzi (DTUs 1 to 6) showed variation in tissue damage and immune response between the acute and chronic phases of the infection. Another limitation of our study may have been the choice of outbred animals that, due to the fact that they are not isogenic animals and not free of specific pathogens (SPF), the genetic variability between individuals is large, allowing for greater disease resistance and requiring a greater number of animals for a robust result [ 60 , 61 ]. Therefore, it is possible that in our model, and with the use of outbred mice, the electrocardiographic changes observed were less pronounced and the use of a chronic phase model and isogenic mice, which has greater genetic homogeneity [ 62 ] and possibly increased susceptibility, needs to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Santi-Roca (2017) [ 59 ] observed that BALB/c mice infected with different strains of T. cruzi (DTUs 1 to 6) showed variation in tissue damage and immune response between the acute and chronic phases of the infection. Another limitation of our study may have been the choice of outbred animals that, due to the fact that they are not isogenic animals and not free of specific pathogens (SPF), the genetic variability between individuals is large, allowing for greater disease resistance and requiring a greater number of animals for a robust result [ 60 , 61 ]. Therefore, it is possible that in our model, and with the use of outbred mice, the electrocardiographic changes observed were less pronounced and the use of a chronic phase model and isogenic mice, which has greater genetic homogeneity [ 62 ] and possibly increased susceptibility, needs to be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we used outbred CD-1 mice rather than widely used inbred C57BL/6 mice. We have consciously made this decision as it is now widely accepted that "the use of inbred mice to model human disease is tantamount to using multiple copies of one individual" (146,147).…”
Section: Discussionmentioning
confidence: 99%
“…However, care should be taken when interpreting the outcomes in these models because of redundancy in the immune system or compensatory hyperactivity that can lead to confounding effects [87]. In addition, scientists have to keep in mind that the use of such genetically modified or defined mice under standardized environmental conditions may influence host immunity and inflammation [88]. While the generation of such mice still remains complicated, expensive, and time consuming, they represent very useful biological tools for studying the host immune response to Pneumocystis.…”
Section: Selection Of the Regimen Inducing Susceptibility To Pneumocystis Pneumoniamentioning
confidence: 99%